Kemampuan Kognitif Siswa dalam Pembelajaran Discovery Learning melalui Soal Literasi-Geometri - Rosida, Lailatur; Mukti, Taufiq Satria (Universitas Pendidikan Ganesha, 2023)
This study aims to determine students' cognitive abilities in discovery learning through geometric-literacy questions in class VIII MTsN Batu City. The study used a quasi-experimental quantitative approach to students in class VIII-G and VIII-H who were selected through a random sampling technique. Data collection techniques used were cognitive tests in the form of descriptions and semi-structured interviews. While the data analysis technique used the independent t test through the prerequisite test in the form of the Kormogrov-Smirnov normality test and the Cronbach alpha reliability using the SPSS version 24.0 application. The results showed that there were two categories of cognitive abilities in discovery learning through geometric-literacy questions in the experimental class, namely (1) students with high cognitive abilities were at stage C6 and numeration level 6 in the form of communication, mathematical, reasoning, argument and choosing strategies . (2) students with moderate cognitive abilities are at stage C5 and numeracy level 4. In the form of mathematical, reasoning, communication, and strategy selection abilities.